Chronic low level trimethyltin exposure and the risk of developing nephrolithiasis. Issue 8 (23rd May 2013) - Tang, Xiaojiang; Li, Nanchun; Kang, Lisha; Dubois, Amber M; Gong, Zhihong; Wu, Banghua; Lai, Guanchao; Yang, Aichu; Ruan, Xiaoling; Gao, Hongbin; Zhu, Guanghua; Ge, Yichen; et al.
Abstract : Objectives: Nephrolithiasis (kidney stones) is a common disease with the prevalence that is increasing globally. We previously found that trimethyltin (TMT), a by-product of plastic stabilisers, can inhibit the H + /K + ATPase activity in renal intercalated cells and alter urinary pH, which is a known risk factor for nephrolithiasis. In this study, we conducted a cross-sectional analysis to evaluate the impact of chronic low level occupational TMT exposure on nephrolithiasis. Methods: This study included 216 healthy workers with TMT exposure and 119 workers as controls with no TMT exposure. All study participants were administered a questionnaire and underwent a routine clinical examination including an ultrasonographic screening for kidney stones. Exposures were assessed by measuring TMT concentrations in personal air samples, blood and urine. Logistic regression analysis was used to estimate the ORs and 95% CIs for the risk of kidney stones. Results: TMT exposed workers had a higher prevalence of kidney stones (18.06%) in comparison with control workers (5.88%). High TMT concentrations in personal air samples, blood and urines were positively associated with increased prevalence of kidney stones in workers exposed to TMT compared with controls workers (p-trend values=0.005, 0.008 and 0.002, respectively). The length of employment in plants with elevated TMT levels (duration of the exposure) was significantly associated with the increased prevalence of kidney stones (p trend=0.001). The ORs were 2.66 for <3 years, 3.73 for 3–<10 years and 7.89 for 10+ years of employment compared with control workers. Conclusions: To our knowledge, this is the first report to demonstrate that occupational exposure to TMT is a potential risk factor for nephrolithiasis.